Antibacterial activity assays of a new cadmium complex with o-phenanthroline and cyanoguanidine: Crystal structure,fluorescence properties, and chemical speciation studies - López Tévez, Libertad Leonor (2011)
A new coordination complex, aqua bis(o-phenanthroline) cadmium(II) sulfate cyanoguanidine pentahydrate, [Cd(o-phen)2(SO4)(H2O)](cnge).5H2O, was synthesized and characterized. The crystal structure was solved by X-ray diffraction methods. It crystallizes in the monoclinic space group P21/n with a=13.7650(2) A°, b=10.2796(2) A2°, c=21.4418(3) A°, β=90.106(2), and Z=4 molecules per cell unit. The cadmium(II) is in a distorted octahedral environment coordinated to two nearly planar and mutually perpendicular o-phenanthrolines, one oxygen atom of sulfate, and a water molecule. Non-bonded and planar cyanoguanidine and five crystallization water molecules complete the asymmetric unit. Vibrational (FT-IR and FTRaman) spectroscopies and thermogravimetric determinations support this structure. Intensity enhancement of the fluorescence spectrum may be a demonstration of the interaction of the metal with phenanthroline. In solution the coordination behavior is rather different, and the speciation studies point to coordination of both cnge and phenanthroline to cadmium. The improvement of the antibacterial activity of cadmium upon complexation has been determined.